HUBUNGAN BUDAYA MASYARAKAT DENGAN TINGKAT KECEMASAN PADA PASANGAN INFERTIL DI RSIA ANNISA JAMBI TAHUN 2015 - Bri Novrika (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Differences in the culture of patriarchal or matriarchal society can influence the way people view the couple with infertility problems and the importance of the existence of children in a family. This study aims to determine the relationship between the culture of the community with anxiety levels in infertile couples at RSIA Annisa Jambi. The type of this study was cross sectional, with a sample of 76 female infertile couples who experienced anxiety with total sampling technique. Data analysis with chi square test. The result of this research shows that there is a cultural relation (p = 0,000) with anxiety level on infertile couple. It is expected that hospitals providing infertility treatment services to provide therapy through psychiatric nursing psychoeducation therapy and / or supportive therapy to infertile couples so as to assist in minimizing the anxiety experienced and support the treatment program undergone infertile couples.Keyword : Community culture, Anxiety, Infertile couples